2019
DOI: 10.1108/jaoc-02-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and organizational change: IASB’s response to the financial crisis

Abstract: Purpose The purpose of this study is to examine the International Accounting Standards Board (IASB)’s response to criticism and political pressure at the time of the global financial crisis through the lens of legitimacy theory. Design/methodology/approach This study constructs a thick description about a causal mechanism between social crisis and organizational change using a process-tracing approach that combines a historical narrative and a theoretical consideration. Findings The IASB faced criticism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
11
0
3
Order By: Relevance
“…El process-tracing viene siendo utilizado con creciente frecuencia en las ciencias de la gestión y el estudio organizacional, incluyendo varios trabajos sobre cuestiones estratégicas (Derbyshire, 2020;Kusano & Sanada, 2019;Nguyen, Chileshe, Rameezdeen, & Wood, 2019;Rey-García, Calvo, & Mato-Santiso, 2019;Muñoz, Cacciotti, & Cohen, 2018;Tessem, 2018;Dossa & Kaufer, 2014). Desafortunadamente, son escasos los trabajos que se ocupan de analizar sus fortalezas metodológicas, ponderar su aporte a la disciplina, e ilustrar analíticamente su aplicación en estudios concretos, más aún en la región iboeroamericana.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…El process-tracing viene siendo utilizado con creciente frecuencia en las ciencias de la gestión y el estudio organizacional, incluyendo varios trabajos sobre cuestiones estratégicas (Derbyshire, 2020;Kusano & Sanada, 2019;Nguyen, Chileshe, Rameezdeen, & Wood, 2019;Rey-García, Calvo, & Mato-Santiso, 2019;Muñoz, Cacciotti, & Cohen, 2018;Tessem, 2018;Dossa & Kaufer, 2014). Desafortunadamente, son escasos los trabajos que se ocupan de analizar sus fortalezas metodológicas, ponderar su aporte a la disciplina, e ilustrar analíticamente su aplicación en estudios concretos, más aún en la región iboeroamericana.…”
Section: Discussionunclassified
“…En estos estudios, la mayoría tiene un enfoque cuantitativo (testeo experimental mediante simulación por computadora, rastreo del cursor, registro de navegación, rastreo ocular y protocolos verbalizados, entre otros), y solo 13 publicaciones en Scopus y 11 en Web of Science adoptan la aproximación cualitativa materia del presente trabajo, todas ellas publicadas recién en los últimos cinco años. Estos estudios cubren un amplio espectro de temas que incluyen innovación (Liu, 2019;Di Paola & Spena, 2019;Makarevich, 2017), sostenibilidad (Muñoz, Cacciotti, & Cohen, 2018;Dossa & Kaufer, 2014), diseño de procesos (Soutrisna & Goulding, 2019), planeamiento (Derbyshire, 2020), capacidad institucional (Evans, 2017), cambio organizacional (Kusano & Sanada, 2019), gestión de riesgo (Timmer & Kaufmann, 2019), alianzas estratégicas (Rey-García, Calvo, & Mato-Santiso, 2019), gestión de stakeholders (Nguyen, Chileshe, Rameezdeen, & Wood, 2019) y satisfacción del consumidor (Tessem, 2018). Conviene notar que todos estos trabajos están publicados en inglés y no se ocupan de organizaciones en la región iberoamericana.…”
Section: Relevancia Para El Análisis Organizacionalunclassified
See 1 more Smart Citation
“…In Kim, Si Xia, and Zhang (2018) study found that hedging can reduce a company's information imbalance and reduce the risk of financial collapse through curbing pessimistic expectations as well as reducing excessive investment. As a result of the global financial crisis, the IFRS Board has faced serious criticism of accounting standards for financial instruments (Kusano & Sanada, 2019). However, studies by many authors, notably Li, Sougiannis, and Wang (2017), Chang, Donohoe, and Sougiannis (2016), Gumb, Dupuy, Baker, and Blum (2018), Schwarzbichler, Steiner, and Turnheim (2018), testify to information advantages of formation of financial statements under IFRS for the purposes of management of financial instruments on the basis of increase of prognostic value of reporting information.…”
Section: Problem Statementmentioning
confidence: 99%
“…(and some of them have come into force). These new standards and changes are the result of the Board's longstanding efforts to provide an adequate response to the reporting problems posed by the 2008 financial crisis (Ball, 2016), (Kusano & Sanada, 2019). They are also the result of an effort to improve the quality of the financial statements prepared in accordance with International Accounting Standards / International Financial Reporting Standards (IAS/IFRS) and for better communication with the users of financial statement information.…”
Section: Introductionmentioning
confidence: 99%